Effects of tractor speeds on the performance of a kenaf harvesting machine - Dauda, Solomon Musa; Ahmad, Desa; Abdan, Khalina; Othman, Jamarei (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Kenaf (Hibiscus cannabinus L.) may next be an industrial crop based on research findings about its technical and commercial potentials. Field equipment for harvesting kenaf continues to be an important aspect of commercialization. Various studies have drawn attention to the need to develop an efficient kenaf harvesting machine. In this study, a rotary serrated cutting system kenaf harvesting machine developed at Universiti Putra Malaysia and kenaf varieties V36 and Fh 952 were used for the experiment. The effects of tractor speeds on the performance of the machine were investigated. Seven different tractor speeds, 2.0, 2.5, 3.7, 4.6, 5.8, 6.9, and 7.7km/hr were used based on the results of the experiments, the tractor speed had significant effect on the performance of the machine in terms of its effective field capacity and the machine capacity. The optimum operating forward speed that gave the highest efficiency of 76% was 3.7 km/h.